2018
DOI: 10.4038/jnsfsr.v46i2.8422
|View full text |Cite
|
Sign up to set email alerts
|

Optimising a solvent system for lipid extraction from cyanobacterium Microcystis spp.: future perspective for biodiesel production

Abstract: Due to unsustainability of petro derived fuels, the eco-friendly energy production. As a successful alternative energy, biodiesel plays a major role to replace petrodiesel. production of biodiesel from biomasses depends on upstream processes. Lipid extraction should be effective and energy production. optimise the lipid extraction solvent system from cyanobacteria. Microcystis systems n-hexane, chloroform: methanol (2:1), n-hexane: ethanol (3:2), chloroform: n-hexane (1:1), dichloromethane: methanol (1:1), n-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Cyanobacteria provide protection to crops against bacteria, insects, and other organisms due to their antimicrobial, allelochemical, and antioxidant properties (Gonçalves, 2021). Free fatty acids (FFAs) derived from cyanobacteria are extensively explored for biodiesel production (Madusanka and Manage, 2018). Polysaccharides have a preponderant role in the improvement of soil quality, with major properties like soil conditioner, nutrient carrier, and a safe release of agrochemicals.…”
Section: Production Of Secondary Metabolitesmentioning
confidence: 99%
“…Cyanobacteria provide protection to crops against bacteria, insects, and other organisms due to their antimicrobial, allelochemical, and antioxidant properties (Gonçalves, 2021). Free fatty acids (FFAs) derived from cyanobacteria are extensively explored for biodiesel production (Madusanka and Manage, 2018). Polysaccharides have a preponderant role in the improvement of soil quality, with major properties like soil conditioner, nutrient carrier, and a safe release of agrochemicals.…”
Section: Production Of Secondary Metabolitesmentioning
confidence: 99%
“…It is critical for the biodiesel sector to continually enhance the elements that will enhance the opportunities for stronger market penetration to attempt for the solving of the financial disadvantages. 73 A successful option originated for lipid biodiesel-convertibles is microalgae. Several photosynthetic bacteria that can store large quantities of lipid—up to 50% of dry tissue weight are available in certain species.…”
Section: Applications Of Renewable Energy From Biomass Wastesmentioning
confidence: 99%
“…Total world energy supply via fossil fuels (oil, coal, and gas) represents 80% of energy sources, followed by renewables and nuclear energy; 18% and 2% respectively (WBA Global Bioenergy Statistics, 2018). Since fossil fuel is non-renewable and finite in quantity, scientists found that fossil fuel reserves of oil, natural gas, and coal will be depleted in approximately 35, 37, and 107 years respectively (Madusanka & Manage, 2018). Therefore, the world is moving towards renewable energies such as biofuel (Madusanka & Manage, 2018), hydropower (Balkhair & Rahman, 2017), wind (Zeng et al 2019), tidal and waves (Niegel, 2018), and Ocean Thermal Energy Conversion (OTEC) (Ahmadi, Dincer & Rosen, 2015), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Since fossil fuel is non-renewable and finite in quantity, scientists found that fossil fuel reserves of oil, natural gas, and coal will be depleted in approximately 35, 37, and 107 years respectively (Madusanka & Manage, 2018). Therefore, the world is moving towards renewable energies such as biofuel (Madusanka & Manage, 2018), hydropower (Balkhair & Rahman, 2017), wind (Zeng et al 2019), tidal and waves (Niegel, 2018), and Ocean Thermal Energy Conversion (OTEC) (Ahmadi, Dincer & Rosen, 2015), etc. due to having lower environmental impacts, Bandara, 2019) carried out in Sri Lanka regarding bioethanol production through the biological pathway and cost-effective processes for converting cellulosic biomass to fuels are yet to be fully realized.…”
Section: Introductionmentioning
confidence: 99%